Asymptomatic Post-Traumatic Rupture of the Right Diaphragm Dome - E. A. Losik; M. V. Fadeeva; V. V. Shchegelsky; R. T. Rzaev; A. V. Stepanov; K. B. Puzakov; M. R. Skhirtladze (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim.  This paper is aimed at presenting the materials of clinical observations associated with diagnosing rare-occurring ruptures of the right dome of the diaphragm that have been overlooked for a long period.Results.  A 61-year-old man was admitted to hospital with a diagnosis of chronic heart failure. Chest radiograph revealed a high position of the right dome of the diaphragm. Computed tomography revealed a defect in the central parts of the diaphragm on the right, the liver was rotated outward with its visceral surface deployed anteriorly and upward. In the right thoracic cavity, anterior to the liver, were the loops of the intestine and the outlet of the stomach.More than 30 years before, the patient had experienced an explosive trauma, which might have caused a rupture in the right dome of the diaphragm. A 70-year-old man, a smoker with a ten-year history of hypertension, was hospitalized with an increase in dyspnea, a cough with the discharge of purulent sputum, the feeling of heaviness behind the sternum. Chest radiograph revealed a high standing of the right dome of the diaphragm at the level of 3rd rib with a decrease in the volume of the right lung, and an increase in cardiac silhouette (cardiothoracic index 0.64). Computed tomography revealed a high standing of the right dome of the diaphragm as well as the compression of the middle and lower lobe of the right lung with the presence of compression atelectasis. The liver was rotated, displaced into the right thoracic cavity, the deformation of the inferior vena cava to the right was visualized due to the displacement and rotation of the liver. The consolidated fractures of 10th–12th ribs on the right were visualized. The patient had had a chest injury resulting from a traffic accident about 15 years before, with no X-ray examination having been conducted at that time.Conclusion.  In the case of left-sided diaphragm ruptures, which are much more frequent than the right-sided ones, the stomach, large and small intestines as well as spleen are displaced into the thoracic cavity. In the case of rightsided diaphragm ruptures, the liver and gallbladder are displaced into the thoracic cavity. Right-sided posttraumatic diaphragmatic hernias that are not diagnosed at the time of injury or trauma and continue to be asymptomatic for a number of years are very rare. The sensitivity and specificity of computed tomography for the diagnosis of diaphragm ruptures is 61–87 % and 72–100 %, respectively. In an acute period, the treatment of diaphragm ruptures is surgical. However, in long-term asymptomatic ruptures, expectant management is possible, particularly if the risk of surgical treatment is high.